PENGARUH PROGRAM SUCCESS FOR ALL TERHADAP KETRAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV MADRASAH IBTIDAIYAH - Ismi Choiron Annisa (Universitas Islam Darul 'Ulum Lamongan, 2019)
Abstract This research has purpose to know the effect of success for all programs toward the ability of students reading comprehension skill of class IVaMIM 21 Kapas Bojonegoro. The kinds of experiments that used in this researchis quasi-experimental design usingpretest-posttest control group design. Data analysis that used is valildity test expert shows that the feasibilityof using the research instrument, validity test ,reliability, homogeneity test and t test shows that the price of t <t table is 4.73 <2.39 , it means that there is sicnifikansof treatment giving. The Calculation of path analysis shows that the response of the parents reading independently affect the result of the dependent variable that is evidenced by the calculated probability value less than 0.05 probability value calculated through linear regression by using SPSS. Therefore, it can be concluded that the existence of independent and intervining variables are effectedtoward students reading comprehension skills.